DEVELOPING E-NIPA (EDUKASI NILAI PANCASILA) APPLICATION TO IMPROVE THE FIFTH-GRADE STUDENTS’ UNDERSTANDING OF PANCASILA VALUES - Sultan Ahmad; Atep Sujana; Rana Gustian Nugraha (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of fifth-grade students’ understanding of Pancasila values by developing the e-NIPA (Edukasi Nilai Pancasila) application, which is an android application that is appropriate for students’ interests and abilities. This application can be operated by students without using an internet network. The research was conducted because the fifth-grade students did not understand Pancasila values in elementary school. The method used in the research is the R&D (Research and Development) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research was conducted on fifth-grade students, which consisted of 21 students in one of the elementary schools in Sumedang City. The results of the research indicate that this product is feasible to use after applying the validation by media and material experts in the very good category with a percentage of 95.5%. The results of the research on the research subjects were processed using the Paired Sample T-test by comparing the results of the students’ average pretest and posttest scores, which begins with conducting a normality test on the data. The results imply that the data were normally distributed and there was a difference between the average students’ pretest and posttest scores and it was obtained that the students’ average scores increased at 38% based on N-gain. It implies that the e-NIPA application can improve students’ understanding of the values of Pancasila.